2021
DOI: 10.5194/acp-21-12989-2021
|View full text |Cite
|
Sign up to set email alerts
|

Optical properties of coated black carbon aggregates: numerical simulations, radiative forcing estimates, and size-resolved parameterization scheme

Abstract: Abstract. The formation of black carbon fractal aggregates (BCFAs) from combustion and subsequent ageing involves several stages resulting in modifications of particle size, morphology, and composition over time. To understand and quantify how each of these modifications influences the BC radiative forcing, the optical properties of BCFAs are modelled. Owing to the high computational time involved in numerical modelling, there are some gaps in terms of data coverage and knowledge regarding how optical properti… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 89 publications
5
17
0
Order By: Relevance
“…For ρ BC >1, MAC BC decreases with increased ρ BC , and the rate of decrease is dependent on R BC . The finding of decreased light absorption for ρ BC >1 is consistent with a recent study which also found decreased MAC BC with increasing aggregate size (Romshoo et al, 2021). Best-fit lines for the scaling of MAC BC as a function of R BC are shown as solid lines in Fig.…”
Section: Phase Shift Parameter Controls Light Absorptionsupporting
confidence: 91%
“…For ρ BC >1, MAC BC decreases with increased ρ BC , and the rate of decrease is dependent on R BC . The finding of decreased light absorption for ρ BC >1 is consistent with a recent study which also found decreased MAC BC with increasing aggregate size (Romshoo et al, 2021). Best-fit lines for the scaling of MAC BC as a function of R BC are shown as solid lines in Fig.…”
Section: Phase Shift Parameter Controls Light Absorptionsupporting
confidence: 91%
“…This study provides experimental support for previous theoretical work based on BC as fractal aggregates (e.g., Kahnert, 2010;Adaichi et al, 2010;Kahnert and Kanngießer, 2020;Smith and Grainger, 2014;Romshoo et al, 2021;Liu et al, 2019;Luo et al, 2018). Analysis of various modelling methods for BC particles showed that the selection of an appropriate size representation (polydisperse size method) and an appropriate morphological representation (aggregate morphology) could result in a more realistic prediction of BC's optical properties (s !…”
supporting
confidence: 81%
“…The AAE for the highly aged aerosols measured during the periods of low BC was lower than 1, reaching values as low as 0.2, which is addressed mostly to the aerosol size distribution (large particles) and internally mixed BC particles (Cappa et al, 2016). As shown by modeling studies (Virkkula, 2021), pure BC particles coated by non-absorbing coating can have AAE in the range from <1 to 1.7, depending also on the morphology of the fractal aggregates (Romshoo et al, 2021). The AAE becomes more reliable in periods of higher aerosol concentration levels in the cold period, when it ranged from 0.6 to 1.35.…”
Section: Cold Season Pollutionmentioning
confidence: 96%
“…Furthermore, chemical evolution after the emissions and atmospheric aging (i.e. aerosol mixing state, particle morphology and size distribution) additionally influence aerosol absorption, which can be noticed especially for the long-range transported air masses (Cappa et al, 2016;Saleh et al, 2013;Romshoo et al, 2021). (Forrister et al, 2015) have shown that BrC emitted from wildfires was highly unstable, with 6% of BrC remaining above background levels after two days.…”
Section: Aerosol Station "Island Bely"mentioning
confidence: 99%